The complexities of legal translation in the drafting of bilateral treaties between Italy and English-speaking countries - Loiacono, Rocco; Bertoli, L. (Routledge Taylor & Francis, 2018)
As observed in previous research, the translation of law has played a very important part in the contact between different peoples and cultures in history, and is playing an even more important role in our increasingly globalized world. The problems arising in the translation of bilateral treaties do not appear to have been explored as extensively when compared with the analysis of the translation of equally authentic texts undertaken in national, supranational and international contexts. Therefore, this paper investigates terminological difficulties encountered in the translation of specific provisions in a selection of bilateral treaties entered into between Italy (civil law) and English-speaking countries (common law) to ascertain how translators have attempted to bridge the divide between the different legal cultures concerned. It is hoped that this investigation, by drawing comparisons with translation approaches adopted in multilateral instruments, will highlight problems encountered in the translation of bilateral treaties – a hitherto largely unexplored area of legal translation.